Pengembangan Aplikasi Food Sharing berbasis Android - Bintang Dimas Pambudi Abdul Rozaq; Adam Hendra Brata; Djoko Pramono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Food is the resources used for creature to live. In 2017, seen from the Food Sustainability Index data that every Indonesian people produce 300 kilograms of food waste in a one year period, which can be mentioned that Indonesians have excess food so many are wasted. Food waste is one of the activities not to consume proper food sources such as being left stale or discarded. The problem of food waste that can be solved by using a smartphone, where almost all people already use a smartphone for their daily activities. Smartphone is used because of its high mobility and can be carried anywhere. From the problem of food waste, the writer has an idea to create a food sharing application by utilizing a smartphone with Android operating system because it is have advantages like internet, camera sensors and GPS (Global Positioning System) sensors. Food sharing application is an application that is developed that is expected to reduce food waste which brings people who surplus of food and people as food recipients so that food is still feasible can be consumed and not thrown into garbage. Testing the application is required because smartphone users with the Android operating system consist of various types of devices with different specifications, then compatibility testing is using the firebase test lab with automatic robotest features to test all of the function automatically.